Fabrication of substituted Y-type hexaferrites/carbon dots composites for recording media and photodegradation of dye. Issue 19 (1st October 2022) - Khan, Kamran; Batool, Zahida; Manzoor, Sumaira; Ahmad, Dilshad; Aman, Salma; Alhashmialameer, Dalal; Abd El-Gawad, Hala H.; Taha, T.A.; Ashiq, Muhammad Naeem
Abstract: The normal microemulsion approach was employed for the synthesis of SrBaZn2-x Mnx Fe12-2y Sny Niy O22 (x = 0.0, 0.25, 0.5, 0.75, and 1.0) while the hydrothermal method was used to synthesize the carbon dots (CDs) and their nanocomposite. The structural characteristics, architectures and surface area of the materials are examined by using various techniques. The magnetic features i.e. magnetic remanence (Mr) and saturation magnetization (Ms) increase up to x, y = 0.5 while the coercivity (Hc) decreases which is explained based on-site occupation of substituents and super-exchange interactions. The electrical resistivity of the substituted ferrite materials also increased from 24.62 to 46.76 × 10 6  Ω cm. The increment in saturation magnetization, remanence, and electrical resistivity suggests that ferrite material can be utilized for high-density recording media as well as for microwave devices. The composite materials with composition SrBaZn1 .5 Mn0·5 Fe11 Sn0·5 Ni0·5 O22 /CDs with different ratios have been employed as photocatalysts for the degradation of Rhodamine B under sunlight. Rhodamine B (RhB) was effectively degraded by photocatalysts with a low CDs content i.e. 5.0 wt percent. The composite degrades the dye up to 96% in 80 min and also showed excellent stability after five consecutive runs. The composite material can be employed for the removal of environmental pollutants using natural sunlight for future applications.